An overview of cancer and beliefs about the disease in Indigenous people of Australia, Canada, New Zealand and the US - Shahid, Shaouli; Thompson, Sandra (Wiley-Blackwell Publishing Asia, 2009)
Objective: Cancer among Indigenous populations in the developed world appears to have increased during last few decades. This literature review explores identified issues related to cancer among the Indigenous populations of Australia, Canada, New Zealand and the United States and examines variations in the epidemiology, Indigenous peoples' perceptions about cancer and potential impacts on care-seeking behaviour. Methods: A search of peer-reviewed journal articles, government reports, published and unpublished theses, and other grey literature was undertaken using electronic databases and citation snowballing. Both epidemiological and qualitative studies were included. Results: Cancer in Indigenous populations in these four countries is characterised by high incidence and mortality rates for specific cancers and lower survival rates as a result of late diagnosis, lower participation and poorer compliance with treatment. A higher prevalence of many cancer risk factors occurs across these populations. Fear of death, fatalism, payback, shame and other spiritual and cultural issues are among Indigenous perceptions of cancer influencing participation in cancer screening and treatment. Conclusions and Implications: The holistic approach (physical, mental, emotional and spiritual) to healing and well-being, and the concept that individual, family and community are inseparable underpin Indigenous care-seeking behaviour. Further community-based research is needed to increase understanding of the needs of Indigenous people with cancer, and to guide policy and practice towards more supportive and effective care. Australia could learn much from the approach to cancer-related issues occurring in Indigenous populations in other developed countries.